TINGKAT PENGETAHUAN MAHASISWA UMSU TENTANG PENCEGAHAN COVID-19 - AHWANI ANNISA SIAGIAN; SITI MASLIANA SIREGAR (LP2MTBM MAKARIOZ, 2023)
COVID-19 is a disease caused by infection with SARS-CoV-2. The spread of COVID-19 also varies from droplets and now through airborne. And the importance of preventing COVID-19 for the community is increased, especially students because students must provide information to the wider community.To determine the level of knowledge of UMSU students about COVID-19 prevention. This research is a cross-sectional study. The research sample was taken using the cluster random sampling method, totaling 369 people. The hypothesis was tested using a questionnaire on the level of knowledge of COVID-19 prevention. The results show that there are 94% (346 people) of respondents who have good knowledge about COVID-19. The results also show that there are 6% (23 people) of respondents who have poor knowledge about COVID-19 prevention. UMSU students have a good level of knowledge about COVID-19 prevention.